2009
DOI: 10.1302/0301-620x.91b5.21525
|View full text |Cite
|
Sign up to set email alerts
|

Premature failure of Kinemax Plus total knee replacements

Abstract: We describe a cohort of patients with a high rate of mid-term failure following Kinemax Plus total knee replacement inserted between 1998 and 2001. This implant has been recorded as having a survival rate of 96% at ten years. However, in our series the survival rate was 75% at nine years. This was also significantly lower than that of subsequent consecutive series of PFC Sigma knee replacements performed by the same surgeon. No differences were found in the clinical and radiological parameters between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A recent study has shown the catastrophic consequences of increased PE wear, leading to a high failure rate in a contemporary TKA design [23, 24]. Therefore, the problems of excessive wear are not only a problem of the past [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown the catastrophic consequences of increased PE wear, leading to a high failure rate in a contemporary TKA design [23, 24]. Therefore, the problems of excessive wear are not only a problem of the past [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Some free radicals remain and initiate an oxidation cascade that occurs in air during shelf‐storage, and during in vivo use . Oxidation causes chain scissioning and embrittlement leading to reduced toughness, increasing the possibility of fatigue fracture during in vivo use, especially in knees . Manufacturers have employed post‐irradiation thermal treatments to reduce or eliminate these free radicals by annealing below the melt temperature or remelting the irradiated UHMWPE.…”
Section: Introductionmentioning
confidence: 99%
“…6 Oxidation causes chain scissioning and embrittlement leading to reduced toughness, 7,8 increasing the possibility of fatigue fracture during in vivo use, especially in knees. 9,10 Manufacturers have employed post-irradiation thermal treatments to reduce or eliminate these free radicals by annealing below the melt temperature 11,12 or remelting 13 the irradiated UHMWPE. Neither method has proved to be without associated problems.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Premature wear of UHMWPE tibial inserts is one of the major causes of failure of TKRs. 6,7 Moreover, particulate wear debris released from polyethylene may also trigger a biological response resulting in osteolysis and/or aseptic loosening of the implant. [8][9][10][11][12] The contemporary tibial component in a TKR can either be a fixed-or a mobilebearing design.…”
mentioning
confidence: 99%